If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-12=h/4+-9
We move all terms to the left:
-12-(h/4+-9)=0
We add all the numbers together, and all the variables
-(h/4-9)-12=0
We get rid of parentheses
-h/4+9-12=0
We multiply all the terms by the denominator
-h+9*4-12*4=0
We add all the numbers together, and all the variables
-1h-12=0
We move all terms containing h to the left, all other terms to the right
-h=12
h=12/-1
h=-12
| 9-2n=-3n | | 9(x-1)/15=3(x+4)/10 | | 6a–18=30 | | 5y-4+y+44=8y+40-6y | | -7(7x-5)=-49x+35 | | (x-4.9)+(0.5x)=x-4 | | (35x-45)/5+3x=10-9x | | 2m-3.01=9.79 | | 150/7x=120/5x | | 2x²+7x+66=0 | | 14d=14+3d | | 5.5+0.45a=6-0.5a | | -x²+80x+900=0 | | (5x+11)=26 | | 0.6x+2=12 | | -115-6x=-13+60 | | 43=19+8c | | X+3y+12=0 | | 3.8x+40.9=17.3-8.0x | | 7t=15t | | 5=x+2x-1 | | k/4-45=50 | | 0=-7c+7c | | 6m+7-2m=13 | | -93-2x=5x+159 | | 36=3(14)+3w | | s/5+2=8 | | 2)n−3n=14−4n | | -2n+20=-n-20+20 | | 8x+4=-8x-8x | | 30+6p=-7(p-5) | | -18s-1=-15-16s |